Supporting vocational students' development of preventive behaviour at work: A phenomenological analysis of teachers' experiences - Alexandra Lecours; Pierre-Yves Therriault (International Journal for Research in Vocational Education and Training (IJRVET), 2017)
Statistics indicate that even if young workers complete vocational training, as a group they are at risk of sustaining injury. It appears that a lack of training in the area of injury prevention may explain some of this effect. Teachers are considered to be key actors in injury-prevention training and in the process of developing students' preventive behaviour at work, but little is known about the reality. The objective of this study was to understand how teachers experience their activities in support of students' development of injury-prevention behaviour at work. Semi-structured interviews were conducted with eleven teachers from four different vocational training programs. The content of the interviews was then examined using phenomenological analysis. Results show representations participants form of occupational health and safety, of injury-prevention behaviour and of their roles as teachers in relation to prevention. A closer look at these roles reveals the daily challenges teachers encounter. Among other things, there seems to be a lack of continuity in the training process, insufficient pedagogical resources and resistance on the students' part. Results offer an insight into teachers' experience with their part in the support of vocational students' development of injury-preventing behaviour. It appears they recognize having to play an active role in the development of injury-preventing behaviour at work among students, but have to face daily challenges affecting their teaching. Results of this study can serve as a starting point to make improvements to the injury-prevention training offered in vocational training centres.
Keywords: 330; VET; Vocational Education and Training; Occupational Health and Safety; Prevention Training; Preventive Behaviour at Work; Teachers; Vocational Training; Young Workers